EFFECT OF THE PROBLEM BASED LEARNING MODELS ASSISTED BY LKPD TO IMPROVE HIGH SCHOOL STUDENTS' CRITICAL THINKING SKILLS ON THE NATURE OF PHYSICS AND MEASUREMENT - Rahmatullah, Delia Syawitri (PILLAR OF PHYSICS EDUCATION, 2024)
Education in the 21st Century guides the development of education. One of them is the ability to think critically. A learning model that can improve students' critical thinking skills is the Problem Based Learning model. The Problem Based Learning model that is applied must have supporting teaching materials, namely LKPD. This research aims to see the effect of the problem based learning model assisted by LKPD on the critical thinking abilities of class X Senior high school students. The type of research is quasi experimental with posttest only Control Design. The research population was the entire class X SMAN 2 Lubuk Sikaping TP 2023/2024. Sampling was taken using purposive sampling technique. The research took two sample classes which were used as the experimental class and the control class. Providing critical thinking final test essay sheets to the two sample classes revealed differences in students' critical thinking abilities. Data analysis shows that the average critical thinking skills of the experimental class is greater than the control class, namely 76.23 > 68.8. The results of the test analysis showed that the two sample classes were normally distributed and had homogeneous variances. The th test result of 2.91 with a tt 2.00 shows that the this outside the Ho acceptance area, meaning that H1 is accepted at a real level of 0.05. So it can be concluded that there is an influence of using the Problem Based Learning model assisted by LKPD to improve students' critical thinking skills.